CLASS CONFLICT ANALYSIS IN QAISRA SHAHRAZ'S ZAMINDAR'S WIFE: A MARXIST PERSPECTIVE - Santoso, Daffa Akbar Dejavu; Ardine, Athiyyah Amirah (Universitas Negeri Surabaya, 2025)
This study examines class conflict in Qaisra Shahraz's short story Zamindar's Wife (2013) through Marxist literary criticism. Employing qualitative content analysis based on Karl Marx and Friedrich Engels' class conflict theory, the research identifies two primary manifestations of exploitation: psychological coercion through which the landlord Sarfaraz manipulates villagers into selling their land, and ideological resistance by Younis, an educated villager who challenges feudal authority. The analysis reveals that Sarfaraz's lavish dinner invitation serves as a tool of domination, creating false obligations that pressure economically dependent villagers into compliance. Conversely, Younis's refusal to attend the dinner and his rejection of land transfer agreements demonstrate how education fosters class consciousness, enabling the oppressed to recognize and resist structural inequalities. The findings highlight education as a critical catalyst for class resistance, illustrating that awareness transforms individual defiance into collective challenge against entrenched feudal systems. This research contributes to literary scholarship by offering a comprehensive Marxist analysis of class dynamics in South Asian literature, expanding beyond previous gender-focused interpretations to examine structural economic inequalities underlying social conflicts.